2016
DOI: 10.1097/qai.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Expenditures for Persons Living With HIV Enrolled in Medicaid, 2006–2010

Abstract: Background Costs of care for persons living with HIV (PLWH) have been high historically. Cost estimates based on data from one health care site may underestimate total expenditures; using insurance claims avoids this limitation. We used Medicaid claims data to comprehensively assess payments for care for PLWH between 2006 and 2010. Methods Five sites from the HIV Research Network (HIVRN) provided information on patients with Medicaid coverage. Medicaid data were obtained from the sites’ states (MD, NY, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Second, we found that cardiovascular, renal and pulmonary CMs, as well as HCV coinfection, are significantly associated with an increased risk of acute hospitalizations among PWL-HIV, in line with other reports in the literature. 18 , 20 , 46 , 48 These findings contribute to the idea that a more stringent control of such CMs may well be necessary in the setting of chronic management of HIV infection. Although much has been done in terms of research and development of newer antiretrovirals, with a more favorable profile of toxicity in all lines of HAART, efforts to reduce the prevalence of CMs in HIV patients need to be increased rather than reduced.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Second, we found that cardiovascular, renal and pulmonary CMs, as well as HCV coinfection, are significantly associated with an increased risk of acute hospitalizations among PWL-HIV, in line with other reports in the literature. 18 , 20 , 46 , 48 These findings contribute to the idea that a more stringent control of such CMs may well be necessary in the setting of chronic management of HIV infection. Although much has been done in terms of research and development of newer antiretrovirals, with a more favorable profile of toxicity in all lines of HAART, efforts to reduce the prevalence of CMs in HIV patients need to be increased rather than reduced.…”
Section: Discussionmentioning
confidence: 76%
“…Acknowledging the paucity of information about this issue, in our country as well as in other countries, our analysis may be relevant to understand how HIV infection may still be causing health care resources utilization as well as health care expenditure in the present setting, beyond HIV testing, HAART expenditure and continuous efforts to improve high quality retention in care. 18 20 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treating one HIV case costs approximately $38,000 per year, with considerable variation dependent on disease stage. (Fleishman, Monroe, Voss, Moore, & Gebo, 2016) Further, the most recent available data estimates the total lifetime cost of treating one case of HIV to be between $253,000 and $402,000 depending on disease stage. (Farnham et al, 2013) Considering that approximately 9%, or 3,600 new cases of HIV in the US each year identify IDU as risk factor, approximately $136.8 million are spent on new HIV infections just among PWID.…”
Section: Care Access Utilization and Economic Impact Of Idumentioning
confidence: 99%